Side‐effects related to adjuvant CAPOX treatment for colorectal cancer are associated with intermuscular fat area, not with total skeletal muscle or fat, a retrospective observational study. Issue 1 (1st January 2018) - Plas, Rogier L. C.; van Norren, Klaske; van Baar, Harm; van Aller, Carla; de Bakker, Maarten; Botros, Nadia; Witkamp, Renger F.; Haringhuizen, Annebeth; Kampman, Ellen; Winkels, Renate
Abstract: Aims: Chemotherapeutic treatment is regularly accompanied by side‐effects. Hydrophilic chemotherapeutics such as capecitabine and oxaliplatin (CAPOX), often used in colorectal cancer treatment, predominantly accumulate in non‐adipose tissues. Therefore the aim of this paper was to investigate whether body composition and fat infiltration in the muscle (muscle attenuation and intermuscular‐adipose‐tissue [IMAT] content) are associated with chemotherapy‐induced toxicities. Methods: In this retrospective observational study, we collected data from 115 colorectal cancer patients receiving adjuvant CAPOX chemotherapy between 2006 and 2015. Information on cancer characteristics were obtained from the Netherlands Cancer Registry. Diagnostic CT scans were retrieved to assess cross‐sectional areas of skeletal muscle and adipose tissue at the third lumbar vertebrae. Information on dose‐limiting toxicity [DLT] and relative administered dose (as % of BSA‐based‐planned‐dose) were retrieved from medical charts. Associations between body composition, muscle quality and chemotherapy‐induced toxicities were determined using Cox‐regression and linear‐regression analyses. Results: We found that DLT incidence was 90% in our cohort: 50% had their dose reduced, 30% their next cycle postponed, 4% a full treatment stop and 6% was hospitalized at their first DLT. Most common were reductions in oxaliplatin dose whilst keeping the capecitabine dose constant. Cox regression analysis indicated no association between body composition or muscle quality and DLT during the first treatment cycle or time to the first DLT. Multiple linear regression showed that higher IMAT‐index and IMAT muscle percentage were associated with a lower relative administered dose of oxaliplatin. Conclusions: In conclusion; only IMAT, not skeletal or fat area was associated with dose‐limiting toxicities among these CRC patients who received CAPOX treatment.